THE IMPACT OF FOREST FIRES ON SOIL LOSS FROM WATER EROSION IN SERRA DE SANTA HELENA - Meneses, Bruno Miguel (2014)
This work assesses the influence of forest fires on soil loss from water erosion in Serra de Santa Helena, Portugal. It first makes an analysis of the spatial and temporal distribution of fires in this Serra, allowing us to know which areas are most affected and also where there is recurrence. Secondly, it determines the erosion, using the Universal Soil Loss Equation (USLE). This latest assessment considers the variation of the “Covered Soil Factor” that integrates the USLE and the occurrence of fires, first estimating the average annual loss of soil, with soil protected by vegetation, and later without protective vegetation. The results reveal the importance of vegetation cover in reducing soil loss by water erosion, since the biggest loss occurs in the unprotected soil as a result of the destruction of the entire protective layer by fire.